Pengaruh Pelatihan dan Motivasi Terhadap Kinerja Karyawan di Suku Dinas Kependudukan dan Pencatatan Sipil Jakarta Pusat - Muhammad Denira; Hendy Tannady (UNIVERSITAS KALBIS, 2022)
This research aims to identify the training and motivation influence on the performance of the Occupation Service Tribe and the Central Jakarta Civil Record. This research uses quantitative methods with sampling techniques and using simple random sampling in the retrieval of data from the questionnaire. The number of population in research is 120 and using 80 samples of 16 indicators times 5. Data is collected by distributing questionnaires through Google Form given to employees Suku Dinas Kependudukan and Kependudukan Pencatatan Sipil Jakarta Pusat that are sampled. This research shows that training has a positive impact on employee performance and motivation has a positive effect on employee performance as well as training and motivation simultaneously affects employee performance.